Analyzing the ASME BPV Code of Construction Professional Engineer Accreditation Requirements and their impact in Central, South America and Mexico (LACCEI, 2024)
Central, South America and Mexico have about 36 ASME Section VIII U2 certificate holders where their vast majority of engineering degree programmes are not recognized by international engineering accreditation organizations. Additionally, in most Latin American countries the organizations that accredit engineering degree programmes depend on their local Ministry of Education which is part of the government, and thus need to create an independent committee to adhere to the Washington Accord or ENAEE current practices, for a region where it is not required nor supported by the local government and engineering education bodies. Current international code practices for Boiler, Pressure Vessel and Nuclear Construction are moving towards mandating the presence of Certifying Engineers that is in responsible charge for both equipment User Design Specifications (UDS) and Manufacturer’s Design Reports (MDR), in order to guarantee that the design and construction of the pressure-retaining component adhere to the ASME Boiler and Pressure Vessel Code design margin philosophies. However, the lack of international engineering degree programme accreditation within the vast majority of countries located in Central and South America is a barrier that cannot be easily surpassed without the engineers having to undergo a thorough revalidation process within the jurisdiction of a foreign country that has accredited their engineering degree programmes to the Washington Accord or the EUR-ACE seal, in order to enable the engineer to join an international engineering accord such as Engineers Europe, IPEA, APEC or the US and Canada Registered Professional Engineer programme, a mandatory requirement to comply with the required Certifying Engineer qualifications. Therefore, pressure vessels and components construction to ASME Section VIII, Divisions 1 to 3 and ASME Section III in Central, South America and Mexico will go through design, construction and installation. If the application requires a Certifying Engineer to be in responsible charge, subcontracting costs of at least two Certifying Engineers need to be considered to certify the vessel UDS and MDR. This requires contacting and contracting professional engineers outside of their own jurisdictions for vessels that would be specified, constructed, and put in service inside their own jurisdiction. This paper presents the recently approved ASME Section VIII, Divisions 1 and 2 CodeCase 3036 that the authors developed with substantial help from manufacturers, authorized inspection agencies and other interested parties within Central, South America and Mexico to attempt to close the gap in these jurisdictions while international engineering degree programme accreditation is achieved in the region, although not without placing substantial restrictions to locally-registered engineers.